(untitled) (European Journal of Pure and Applied Mathematics, 2017)
Using a generalized spherical mean operator, we obtain a generalization of Younisâ€™s Theorem 5.2 in [12] for the Dunkl transform for functions satisfying the d-Dunkl Dini Lipschitz condition in the space Lp(Rd,wl(x)dx), 1 < p â‰¤ 2, where wl is a weight function invariant under the action of an associated reï¬‚ection group.Â